Mycobacterium avium subsp. paratuberculosis in an Italian Cohort of Type 1 Diabetes Pediatric Patients. (11th July 2012) - Manca Bitti, Maria Luisa; Masala, Speranza; Capasso, Francesca; Rapini, Novella; Piccinini, Simona; Angelini, Federica; Pierantozzi, Andrea; Lidano, Roberta; Pietrosanti, Silvia; Paccagnini, Daniela; Sechi, Leonardo A.
Abstract : Mycobacterium avium subsp. paratuberculosis (MAP) is the etiological agent of Johne's disease in ruminants. Recent studies have linked MAP to type 1 diabetes (T1D) in the Sardinian population. The aim of this study was to investigate the prevalence of MAP infection in a T1D cohort from continental Italy compared with healthy control subjects. 247 T1D subjects and 110 healthy controls were tested for the presence of MAP. MAP DNA was detected using IS900-specific polymerase chain reaction (PCR). The presence of antibodies towards a MAP antigen, heparin binding hemoagglutinin (HBHA), was detected by ELISA. We demonstrated a higher MAP DNA prevalence in plasma samples from T1D patients and a stronger immune response towards MAP HBHA, compared with healthy control subjects. Moreover, in the recent onset patients, we observed an association between anti-MAP antibodies and HLA DQ2 (DQA1 0201/DQB1 0202). These findings taken together support the hypothesis of MAP as an environmental risk factor for the development of T1D in genetically predisposed subjects, probably involving a mechanism of molecular mimicry between MAP antigens and pancreatic islet β -cells.